Mobile Wireless Networks :Challenges (International Journal of Engineering and Computer Science, 2017)
We are seeing demand for broadband services is continuously exploding. So, mobile wireless networks must expand greatly theircapacities. Here we are reviewing the economic and technical challenges associated with wireless networks to meet this explodingdemand. The paper first reviews a brief technical background on mobile wireless networks and these basic methods to deepentheir capacity. We can divide the Methods of capacity expansion into three general categories: the deployment of more radiospectrum; more intensive geographic reuse of spectrum; by increasing the capacity of each MHz of spectrum within a givengeographic area. We find that without significantly increased allocations of spectrum, wireless capacity expansion will be whollyinadequate to accommodate expected demand growth